Sensibility of Stage Design in related with different Performance; Opera, Musical, Play Observational, Qualitative Research; Case Study UK-London - Nashta, Roxaneh Fouladi (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: Theatre performances still have many audiences to attract, which each one of these performances has been presenting for them on divers stages with different design concepts. The objects, which are given to the audience, are an overview of each particular performance, which is the “Stage Design” of those performances. Design of the stages with the performances, which are the actors‘ movements, together it makes the whole sensibility of the space. This research‘s aim is to investigate about the stage designs sensibility in related to different performances. The word “Sensibility” means “The ability to feel or perceive” (Houghton, 2000). In this case, the sensibility can be named as one of the human skills, which helps them to have better understanding of the physical or mental obsessions around them. This study is a qualitative observational research, which took place in London-UK, to get some information nearby differences and similarities, about diverse types of stages and altered performances. Observations were done from twenty different theatres, in three kinds of performances. So the methodology has been done step by step to figure out the main questions of this research which is; What is the sensibility of stage design in each of these particular theatre performances; Opera, musicals and plays? Keywords: Stage Design, Performances, Movement, Audience, Actor and Sensibility. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Tiyatro gösterilerinde sunulan her bir gösteri , farklı tasarım konseptleri ile birçok izleycinin ilgisini çekmektedir. “Sahne Tasarımında” izleyicilere verilen nesnelerin her biri gösterinin genel bakış açısını oluşturmaktadır.Kullanım alanı, sahne tasarımı ve aktörlerin hareketleri ile birlikte bir bütünlük sağlamaktadır. Bu çalışmanın amacı ise; sahne tasarımlarının duyarlılığını farklı performanslarla ilişkili olarak araştırmaktır. “Duyarlılık” kelimesi “hissetmek ve algılama yeteneği” demektir (Houghton, 2000). Bu durum da duyarlılık, çevrelerinin fiziksel veya zihinsel olarak daha iyi anlaşılabilmesine yardımcı olur ve bu da insan becerileri olarak adlandırılabilir. Bu çalışma Londra-İngiltere‘de yapıldı.Niteliksel ve gözlemsel bir araştırmadır. Tezde, çeşitli ve değişken sahnelerin farklılıkları ve benzetmeleri araştırılmıştır. Gözlemler yirmi farklı tiyatro ve üç ayrı performans arasında yapıldı. Bu araştırmanın temel sorunu ise; Opera, müzikal ve tiyatrolarda sahne tasarımının duyarlılığı nedir ? Anahtar sözcükler: Sahne tasarımı, performanslar, hareket, seyirci, aktör ve duyarlılık.
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2012. Supervisor: Assoc. Prof. Dr. Uğur Dağlı.
Keywords: Interior Architecture; Stage - Setting and Scenery; Stage Design - Performances - Movement - Audience - Actor and Sensibility